Three new species of pennatulacean octocorals with the ability to attach to rocky substrata (Cnidaria: Anthozoa: Pennatulacea) - Williams, Gary C.; Alderslade, Philip (Zootaxa, 2011)
All sea pens have been thought to anchor in soft sediment using a basal, sausage-shaped, muscular peduncle. Based on underwater images and examination of specimens, we report an adaptation of the proximal portion of the peduncle for attachment to solid surfaces. We document four species with this adaptation, three new, Anthoptilum lithophilum sp. nov. (California, 669–700 m), A. gowlettholmesae sp. nov. (Tasmania, 729–1803 m), and Calibelemnon francei sp. nov. (the Bahamas, 1969 m), and one known, A. decipiens Thomson & Henderson, 1906 (Sri Lanka, 925 m). The peduncle of a colony with this adaptation is greatly expanded by an outgrowth of the coenenchyme that forms a sucker-like structure, beneath which a conical mass of tough tissue surrounds the proximal end of the internal axis. We infer this structure affects suction, increasing or decreasing the strength of adhesion to the substratum, and discuss the systematics and functional morphology of this new ecological phenomenon—pennatulaceans fastened to hard substrata. We alter the definition of the genus Anthoptilum to accommodate this morphology, reporting on specimens of the type species, A. grandiflorum; compare the two sea pen families—Anthoptilidae and Scleroptilidae— and the two genera; and present a key to the known rock-inhabiting species.